2015
DOI: 10.1007/s12187-015-9342-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Version of the Personal Wellbeing Index-School Children (PWI-SC) in Chilean School Children

Abstract: Child and adolescent measures of the quality of life or subjective well-being are scarce in Latin American countries. Chile is no exception to this situation that represents a gap in the literature for South American countries research. Thus, the aim was to analyze the psychometric properties of the Personal Well-being Index for School Children (PWI-SC) of Cummins et al. Social Indicators Research, 64 (2), 159-190, (2003) in a sample of Chilean school children. We use a sample of 1096 pupils between 10 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
7
0
2
Order By: Relevance
“…First, the cross-sectional nature of the study does not allow any causal conclusions. Of note, while we considered the effects of psychopathology and substance use on SWB, other studies suggested an inverse impact (Alfaro et al, 2016;Huebner et al, 2004). Longitudinal studies are needed to reveal more insight in the bi-directionality of this relationship, which is clearly needed in future research on this topic in Uruguay and Latin-America.…”
Section: Research Limitations and Recommendationsmentioning
confidence: 97%
See 3 more Smart Citations
“…First, the cross-sectional nature of the study does not allow any causal conclusions. Of note, while we considered the effects of psychopathology and substance use on SWB, other studies suggested an inverse impact (Alfaro et al, 2016;Huebner et al, 2004). Longitudinal studies are needed to reveal more insight in the bi-directionality of this relationship, which is clearly needed in future research on this topic in Uruguay and Latin-America.…”
Section: Research Limitations and Recommendationsmentioning
confidence: 97%
“…Fund.,São Paulo,21(4), 486-510, set. 2018 problems, such as depressive symptoms, dissocial behaviour, suicidal intent and suicidal ideation, low self-esteem, and family and peer relationship problems (Alfaro et al, 2016;Suldo & Huebner 2004;Zullig et al, 2001). In addition, low levels of SWB in adolescents have been found to be related to risky behaviour such as drug or alcohol abuse and antisocial behaviour like aggression to others and sexual harassment (Proctor et al, 2009).…”
Section: Relevance Of Studying Subjective Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Se utilizó la escala índice de bienestar personal (PWI), en su versión en español adaptada de la versión española (Casas et al, 2011) para Chile (Alfaro et al, 2016). Esta escala mide la satisfacción con la vida a través de un puntaje global, así como la satisfacción en siete ámbitos específicos.…”
Section: Instrumentounclassified